* PENGARUH LATIHAN POLA TARGET TERHADAP AKURASI SHOOTING PADA PERMAINAN FUTSAL SMAN 1 CIWARINGIN: PENGARUH LATIHAN POLA TARGET TERHADAP AKURASI SHOOTING PADA PERMAINAN FUTSAL SMAN 1 CIWARINGIN - Alfarizi, Ilham; Sudrazat, Adang; Rukmana, Anin (Jurnal Porkes, 2024)
This study aims to examine the effect of target patterns on shooting accuracy in futsal games at the extracurricular SMA Negeri 1 Ciwaringin. This form of research uses quantitative with a form of experimental method and sampling is done using total sampling with a research sample of 20 people. The research research design used a one-group pretest-posttest design. This research was conducted to determine whether or not shooting accuracy in futsal players, the research instrument was a shooting kick test to the target. The research was conducted 12 times a meeting by conducting an initial test (pretest) then given treatment (treatment) 10 times a meeting using a target pattern and then a final test (posttest). The results of the normality test with the Mean of the posttest 11.3 is greater than the pretest 7.45 with a Mean difference of 3.85 so there is a change after being given tereatment. The results of hypothesis testing using the t test, it can be seen that the t value (13.491) > t table (1.699). From the results of the t test Sig value obtained is 0.000 smaller < 0.05, then Ho is rejected and Ha is accepted. So it can be concluded that there is a significant effect of the target game pattern training model on shooting accuracy in extracurricular participants of SMA Negeri 1 Ciwaringin.